Controlling Bacterial Pathogens in Water for Reuse: Treatment Technologies for Water Recirculation in the Blue Diversion Autarky Toilet - Nguyen, Mi T.; Allemann, Lukas; Ziemba, Christopher; Larivé, Odile; Morgenroth, Eberhard; Julian, Timothy R. (Frontiers in Environmental Science, 2017)
The Blue Diversion AUTARKY Toilet is a urine-diverting toilet with on-site treatment. The toilet is being developed to provide a safe and affordable sanitation technology for people who lack access to sewer-based sanitation. Water used for personal hygiene, hand washing, and flushing to rinse urine- and feces collection bowls is treated, stored, and recycled for reuse to reduce reliance on external water supplies. The system provides an opportunity to investigate hygiene of water for reuse following treatment. Treatment in the toilet includes a Biologically Activated Membrane Bioreactor (BAMBi) followed by a secondary treatment technology. To identify effective secondary treatment, three options, including granular activated carbon (GAC) only, GAC+chlorine (sodium hypochlorite), and GAC+electrolysis are considered based on the bacterial inactivation and growth inhibition efficiency. Four different hygiene-relevant bacteria are tested: Escherichia coli, Enterococcus faecalis, Pseudomonas aeruginosa, and Salmonella typhimurium. Our evaluation demonstrates that - despite treatment of water with the BAMBi - E. coli, P. aeruginosa, and S. typhimurium have the potential to grow during storage in the absence of microbial competition. Including the indigenous microbial community influences bacterial growth in different ways: E. coli growth decreases but P. aeruginosa growth increases relative to no competition. The addition of the secondary treatment options considerably improves water quality. A column of GAC after the BAMBi reduces E. coli growth potential by 2 log10, likely due to the reduction of carbon sources. Additional treatments including chlorination and electrolysis provide further safety margins, with more than 5 log10 inactivation of E. coli. However, reactivation and/or regrowth of E. coli and P. aeruginosa occurs under in the absence of residual disinfectant. Treatment including the BAMBi, GAC, and electrolysis appear to be promising technologies to control bacterial growth during storage in water intended for reuse.